Formulation and Characterisation of Ternary Salt Based Solutions as Phase Change Materials for Cold Chain Applications. (February 2019) - Cong, Lin; She, Xiaohui; Leng, Guanghui; Qiao, Geng; Li, Chuan; Ding, Yulong
Abstract: Cold energy storage has attracted considerable attention due to the increasing cooling demand, which provides an isothermal environment for users. Salt-water solutions are suggested as phase change materials (PCMs) for sub-zero applications because they have favourable thermoproperties. Binary salt based PCMs have been widely studied. However, choices are limited for PCMs with the phase change temperature between -15 and -30 °C for cold chains. In this paper, three ternary salt-water solutions (NaCl-NaNO3 -H2 O, NaCl-Na2 SO4 -H2 O and NaCl-KCl-H2 O) are formulated, characterised and compared, where NaCl solution is selected as the base material. The experimental results show that ternary salt-water solutions have lower phase change temperatures than the NaCl solution. NaCl-Na2 SO4 solution has the highest phase change temperature of -21 °C, while NaCl-NaNO3 solution has the lowest value around -27 °C. The fusion heat of the ternary salt-water solutions depends on the components and salt ratio. NaCl-KCl solution has the highest fusion heat among NaCl solution and ternary PCMs, while NaCl-NaNO3 solution shows the lowest fusion heat. NaCl-Na2 SO4 solution does not have a significant difference with NaCl solution due to the limited solubility. Finally, a new approach is proposed for formulating a set of ternary salt based PCMs, which helps to bridge the gap in this temperature range for cold chain applications.